Elastoplastic consolidation beneath shallowly embedded offshore pipelines. Issue 2 (29th June 2012) - Chatterjee, S.; Yan, Y.; Randolph, M. F.; White, D. J.
Abstract : The consolidation response of partially embedded seabed pipelines has been investigated in the past using small-strain finite-element (SSFE) analysis with elastic soil response. This paper presents results from large-deformation finite-element (LDFE) analyses, using the modified Cam Clay plasticity model for the soil, to address the problem more realistically, including initial plastic penetration of the pipe. The effects of initial embedment, pipe–soil interface friction and strength gradient have been explored in a systematic manner and comparisons with the elastic solutions show the influence of non-linearity. Effects of local soil heave on consolidation rate are quantified by comparing results from SSFE and LDFE analyses. The dissipation responses are fitted by simple equations to aid application in design.